Validation of 24-Hour Posaconazole and Voriconazole MIC Readings versus the CLSI 48-Hour Broth Microdilution Reference Method: Application of Epidemiological Cutoff Values to Results from a Global Candida Antifungal Surveillance Program - Pfaller, M. A. (American Society for Microbiology, 2011)
We performed 24- and 48-h MIC determinations of posaconazole and voriconazole against more than 16,000 clinical isolates of Candida species. By using the 24- and 48-h epidemiological cutoff values (ECVs), the categorical agreement between the 24-h and reference 48-h broth microdilution results ranged from 97.1% (C. parapsilosis and voriconazole) to 99.8% (C. krusei and voriconazole), with 0.0 to 2.9% very major discrepancies (VMD). The essential agreement (within 2 log(2) dilutions) between the 24- and 48-h results was 99.6% for both posaconazole and voriconazole. The MIC results obtained for both posaconazole and voriconazole after only 24 h of incubation may be used to determine the susceptibilities of Candida spp. to these important antifungal agents. The applications of ECVs to this large collection of Candida isolates suggests the potential to develop 24-h species-specific clinical breakpoints for both posaconazole and voriconazole.